PENGEMBANGAN APLIKASI “PONTIANAK HERITAGE” BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN SEJARAH - Haris Firmansyah; Sarah Bibi (Jurnal Pendidikan Sejarah Indonesia, 2020)
The purpose of developing the Pontianak Heritage application as an Android-based historical learning media that is able to display the location of cultural heritage, descriptions, and images and Knowing how the quality of applications developed is based on ISO / IEC 25010 software quality testing standards. R&D). Research and development is a process or steps to develop a new product or improve existing products and can be accounted for. The results of this research that this research produces Pontianak Heritage application called Historoid as a history learning media for high school students who are able to display the location of cultural heritage in Pontianak, West Kalimantan, descriptions and images developed on the Android platform using Google Maps technology. The tool used in the application development process is Android Studio and the results of the Historoid application quality analysis results in functional suitability test results are very feasible because all application functions are running 100%.